(untitled) (Pathibhara Journal of Multidisciplinary Research, 2026)
This research investigates the impact of mergers and acquisitions (M&A) on the financial performance of commercial banks in Nepal, a topic of growing relevance in the country’s evolving financial landscape. Drawing on a period characterized by significant policy changes and consolidation efforts by the Nepal Rastra Bank, the study analyzes pre- and post-merger financial indicators, specifically focusing on profitability and risk. Utilizing a descriptive/ causal-comparative research design, the study selected two merged Nepalese commercial banks, NIC ASIA Bank Limited and Global IME Bank Limited, as sample cases, examining their annual financial reports over a fourteen-year period. Key financial ratios such as Return on Assets, Return on Equity, Net Profit Margin, Earnings Per Share, and Market Price Per Share were analyzed using statistical tools including mean, standard deviation, coefficient of variation, and regression analysis. The findings present mixed outcomes: while Global IME Bank demonstrated improved profitability and reduced risk volatility post-merger, NIC ASIA Bank experienced a decline in average profitability ratios, despite increased overall profit, and an increase in risk volatility. This heterogeneity in outcomes suggests that, while mergers and acquisitions can bolster financial institutions, their success is contingent on various factors beyond mere consolidation.